Per-Treatment Post Hoc Analysis of Clinical Trial Outcomes With Tolvaptan in ADPKD - Andrew J. Mallett; Ronald D. Perrone; Gopala Rangan; Carmel Hawley; Ragada El-Damanawi; Thomas F. Hiemstra; Carolina Townsend Arellano; Jennifer Lee; Vicente E. Torres (Kidney International Reports, 2021)
Introduction: In pivotal trials of patients with autosomal dominant polycystic kidney disease at risk of rapid progression, tolvaptan slowed estimated glomerular filtration rate (eGFR) decline in early-to-moderate (TEMPO 3:4 [NCT00428948]) and moderate- to late-stage (REPRISE [NCT02160145]) chronic kidney disease (CKD). Discontinuation was less frequent in REPRISE (15.0%) than TEMPO 3:4 (23.0%), given that in REPRISE, only subjects who tolerated tolvaptan 60/30 mg daily initiated the double-blind phase. We evaluated whether the greater treatment effect in REPRISE was attributable to different completion rates. Methods: We conducted post hoc analyses of TEMPO 3:4 and REPRISE completers, defined as subjects who took trial drug to the end of the treatment period in TEMPO 3:4 (3 years) or REPRISE (1 year). Efficacy (rate of change in eGFR for tolvaptan vs. placebo) was analyzed as in each trial. Subjects from TEMPO 3:4 and REPRISE were also matched by propensity score for age, gender, and baseline eGFR to explore potential additional determinants of treatment effect. Results: The annualized tolvaptan treatment effect in TEMPO 3:4 completers (difference vs. placebo of 0.98 ml/min per 1.73 m2/y) and REPRISE completers (difference of 1.23) was similar to that of the respective total trial populations (TEMPO 3:4: 0.94; REPRISE: 1.27). The treatment effect of tolvaptan was also similar between matched subjects. Conclusion: Greater treatment completion rate did not drive greater treatment effect in REPRISE. The more advanced CKD of REPRISE subjects may be more relevant. More rapid decline in kidney function in later-stage CKD enabled the effects of tolvaptan to be more easily discerned.